Assessment of the degradation of aesthetics Beneficial Use Impairment in the Toronto and region Area of Concern. Issue 3 (3rd July 2018) - Dahmer, S. C.; Matos, L.; Jarvie, S.
Abstract : Toronto and Region was designated a Great Lakes Area of Concern in 1987 due to significant degradation of environmental quality and impaired beneficial uses, including Degradation of Aesthetics. Historically overflows of combined sewers, direct discharge of poorly treated industrial wastewater, contaminated storm water, and litter contributed to excessive floating debris, odour and unnatural turbidity along parts of the waterfront and in some sections of Area of Concern watersheds. Despite the perception of poor aesthetic quality of these waters, little to no monitoring was carried out to assess the Degradation of Aesthetics Beneficial Use Impairment due to the challenge of reporting aesthetics in a quantifiable, unbiased manner. Here we describe the qualitative monitoring program implemented in the Toronto region to assess the aesthetic condition of local watersheds. An Aesthetic Quality Index developed for use by Areas of Concern was adapted by taking advantage of existing monitoring programs and local expertise. Results of the assessment indicate that no persistent objectionable deposit, unnatural colour or turbidity, or unnatural odour was present in the Toronto region during the period of study.